2012
DOI: 10.1029/2011ja017235
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and clock angle control of the location of flux transfer event signatures at the magnetopause

Abstract: [1] Most models of flux transfer event (FTE) formation produce pairs of structures which in general move away from the subsolar region and give rise to signatures which can be observed in both the Northern and Southern Hemispheres. The multiple reconnection line (X line) model is unusual as a reconnection-based model that is capable of producing a single flux rope if only two X lines are present. Raeder (2006) reported the results of an MHD simulation where he studied the effect of the Earth's dipole tilt on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 46 publications
4
35
0
Order By: Relevance
“…The subsequent motion of most FTEs was towards the winter hemisphere. There is observational evidence from both INTER-BALL and Cluster that this effect is indeed present at the magnetopause to some degree (Korotova et al, 2008;Fear et al, 2012), although Fear et al (2012) found that in situ FTE signatures were also observed near equinox, contrary to the Raeder (2006) prediction. If this seasonal bias is present, then this introduces a limit to the use of FTE signatures as a proxy for energy transfer.…”
Section: Palmroth Et Al: Imf B Y and Tilt Dependence Of Energy Trmentioning
confidence: 49%
See 4 more Smart Citations
“…The subsequent motion of most FTEs was towards the winter hemisphere. There is observational evidence from both INTER-BALL and Cluster that this effect is indeed present at the magnetopause to some degree (Korotova et al, 2008;Fear et al, 2012), although Fear et al (2012) found that in situ FTE signatures were also observed near equinox, contrary to the Raeder (2006) prediction. If this seasonal bias is present, then this introduces a limit to the use of FTE signatures as a proxy for energy transfer.…”
Section: Palmroth Et Al: Imf B Y and Tilt Dependence Of Energy Trmentioning
confidence: 49%
“…Note that more FTE signatures were observed when the IMF was southward and dawnward than when it was southward and duskward. This is in part because the IMF was more likely to have a southward/dawnward orientation than a southward/duskward orientation during the interval that was surveyed (Fear et al, 2007), but it is also because Cluster observed the post-noon Northern Hemisphere magnetopause and pre-noon Southern Hemisphere magnetopause (the most likely locations for FTE signatures when the IMF is southward and dawnward) during the local hemisphere's winter (Fear et al, 2012). The events which occur when the IMF is strongly northward are observed at the postterminator magnetopause, and are consistent with an origin at a high latitude reconnection site (Fear et al, 2005).…”
Section: Gumicsmentioning
confidence: 99%
See 3 more Smart Citations